Peran Orang Tua dalam Mengembangkan Kemampuan Bicara pada Anak Speech Delay Usia 4-5 Tahun - Zuhriyah, Ismatuz; Lestari, Gunarti Dwi (J+PLUS UNESA, 2024)
The purpose of this research is to describe the role of parents which includes the role of educator, facilitator, and motivator in developing speaking skills in speech delay children aged 4-5 years. The research method used is descriptive qualitative using data collection techniques, namely interviews, observation and documentation. The data analysis techniques used include data collection, data reduction, data presentation, and verification or drawing conclusions. The resulte obtained from this research indicate that parents are still not optimal in carrying out their role as educators, facilitators and motivators to support the developments of speaking abilities in speech delay children aged 4-5 years because every parent has and experiences inhibiting factors in carrying out their role, such as parents busy to work, unsupportive environment, use of two languages, and other inhibiting factors. The supportting factors provided by parents to be able to develop speaking skills in speech delaye children include providing educational games, conducting speech therapy, consulting with psychologosts, self-therapy, school, and other supporting therapies, such as occupational therapy and behavioral theraphy.